Predation costs and compensations in reindeer husbandry - Pekkarinen, Antti; Tahvonen, Olli; Kumpula, Jouko (Wildlife Biology, 2020)
Conflicts often arise when large predators and free-ranging livestock share a common area. Various compensation schemes arc used to attempt solving these conflicts, but the costs of predation to suffering stakeholders arc often unknown. Semi-domesticated reindeer husbandry and large carnivores form one such system, where conflicts between predator conservation and the traditional livelihood are common. We apply an age- and sex-structured reindeer-lichen model to examine the effects of predation on reindeer management. Based on the previous studies we specify age- and sex-class-specific mortalities due to various predators, and study optimal reindeer husbandry under predation pressure and the costs of predation. We show that the costs of predation highly depend on the age-class-specific killing rates of reindeer by various predator species, but not on interest rate or pasture conditions. Regarding species that are more likely to kill adult reindeer in addition to calves, the total predation costs are clearly higher than the net slaughtering value of the predated animals. The decrease in steady-state yearly net income is highest for the gray wolf and lower for other predator species. Adapting to predation pressure includes increasing the size of the reindeer population in winter and changing the slaughtering age of males towards young adults, thus reducing the importance of calf harvesting. This result contrasts with the previous results from stage-structured models that do not fully include time lags related to long-living ungulate species. The costs of predation appear to be much higher in an ex post system than in a territorial compensation system, as in an cx post system herders have not adapted to the predation pressure and must search for the predated reindeer to gain compensations. Our results suggest that co-existence of a viable gray wolf population and profitable reindeer husbandry in the same area is not possible in most cases. Peer reviewed